2015
DOI: 10.1111/irv.12319
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and virological characteristics of influenza B: results of the Global Influenza B Study

Abstract: IntroductionLiterature on influenza focuses on influenza A, despite influenza B having a large public health impact. The Global Influenza B Study aims to collect information on global epidemiology and burden of disease of influenza B since 2000.MethodsTwenty-six countries in the Southern (n = 5) and Northern (n = 7) hemispheres and intertropical belt (n = 14) provided virological and epidemiological data. We calculated the proportion of influenza cases due to type B and Victoria and Yamagata lineages in each c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
142
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 162 publications
(182 citation statements)
references
References 20 publications
28
142
2
2
Order By: Relevance
“…Consistent with other studies,14, 47, 48 influenza B affected children and teenagers more than adults in the study. We found that 2012 had a higher rate of influenza A notifications, with increased notifications particularly in younger children and older adults.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Consistent with other studies,14, 47, 48 influenza B affected children and teenagers more than adults in the study. We found that 2012 had a higher rate of influenza A notifications, with increased notifications particularly in younger children and older adults.…”
Section: Discussionsupporting
confidence: 93%
“…Influenza B accounted for 17% of total notifications in the study. This is slightly lower than the global proportion, with an average of 20% estimated over a similar period from 26 countries across different geographic regions including Australia 14. In that study, the highest median proportion of influenza B was found in tropical regions and the lowest was in the Southern Hemisphere, but when compared between the geographic regions, the differences were not statistically significant.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations